PARP10 Multi-Site Auto- and Histone MARylation Visualized by Acid-Urea Gel Electrophoresis - Antonio Ginés García-Saura; Herwig Schüler (Cells, 2021)
Poly-ADP-ribose polymerase (PARP)-family ADP-ribosyltransferases function in various signaling pathways, predominantly in the nucleus and cytosol. Although PARP inhibitors are in clinical practice for cancer therapy, the enzymatic activities of individual PARP family members are yet insufficiently understood. We studied PARP10, a mono-ADP-ribosyltransferase and potential drug target. Using acid-urea gel electrophoresis, we found that the isolated catalytic domain of PARP10 auto-ADP-ribosylates (MARylates) at eight or more acceptor residues. We isolated individual species with either singular or several modifications and then analyzed them by mass spectrometry. The results confirmed multi-site MARylation in a random order and identified four acceptor residues. The mutagenesis of singular acceptor residues had a minor impact on the overall auto-MARylation level and no effect on the MARylation of histone H3.1. Together, our results suggest that PARP10 automodification may have functions in the regulation of intramolecular or partner binding events, rather than of its enzymatic catalysis. This contributes to a better understanding of PARP10 functions, and, in the long run, to gauging the consequences of PARP inhibitor actions.